Gáspar Gómez de Toledo and the pursuit of fame - Luis M. Esteban Martín (Celestinesca, 2021)
Gaspar Gómez de Toledo, with his Tercera parte de la tragicomedia de Celestina, intends not only to continue the previous work, the Segunda Comedia de Celestina, by Feliciano de Silva, and thus enter the celestinesque cycle that began with the publication of Celestina, but also to become the author with whom the cycle is definitively closed. Consequently he concludes unfinished episodes in Silva’s work to definitively end with the old pimp Celestina resurrected by Silva. This intention to close a cycle is motivated by the desire for fame, in order to pass into posterity as the author who culminated the adventures of Fernando de Rojas’ procurer and, therefore, to enjoy the success that the public granted to the two works that preceded him.